Understanding Muslim Consumer Through Ads - Women, Money, and Halal: Semiotic Analysis - BaHamburah, Buthaina (2014)
There are about 1.8 billion Muslims around the world, in which almost one in four of the world’s population is a Muslim, and this number is expected to grow by a significant 35% to 2.2 billion in 2030 globally (Ogilvydo, 2014). Hence, the purchasing power of Muslims market is increasing constantly. Global brands dealing with multicultural markets such as the Muslim market face difficulty with respect to the extent to which international marketing strategy is standardized across national borders. This paper seeks to understand how Muslim consumers decode and construct meaning from advertising message. In particular, it explores three controversial issues associated with Islamic culture namely: women’s gender role and sexuality, money and banking system, and Halal concept. Five advertisements are screened and analyzed using semiotic analysis using Stern’s (1996) three steps textual analysis of construction and deconstruction meaning. Findings from the analysis show that standardization of marketing strategy in Muslim market is probably not feasible. Muslims decoding process of advertising message is highly relative to two main sources to Islam: Quran and Sunnah (Prophet Sayings and actions). Therefore, understanding these two sources can help global brands significantly. Furthermore, a clear distinction must be made between Islam as a religion and the culture in which Muslims really practice.